Direct intervention in the foreign exchange market and monetary policy in the Caribbean : signaling or leaning against the wind : draft - Seerattan, Dave ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Looks at whether the relationship between direct intervention and monetary policy in Jamaica, can best be described as 'signaling' or 'leaning against the wind'.